Building the Burlington Bay Canal: The Staples Thesis and Harbour Development in Upper Canada, 1823-1854 - Millard, Rod (Ontario History, 2018)
This article examines the construction of the Burlington Bay Canal, Upper Canada’s first government-financed internal improvement. Designed in 1824 to create an entrance to a natural harbour at the head of Lake Ontario, the canal was an engineering, financial and political fiasco. Using a staples thesis approach, this study explores the reasons for the canal’s problem.